Electrokinetic and gel behavior of Si3N4 aqueous suspension. Issue 7 (1st April 2021) - Yang, Xiaole; Li, Yuanbing; Xie, Hehan; Yang, Xianfeng; Zhou, Zhe
Abstract: Electrokinetic and gel behavior of Si3 N4 aqueous suspension for gel casting were investigated in this study. The zeta potential of dilute and concentrated suspension with organic binder was evaluated innovatively. The influence of the binder composition and solid loading on the gel time and viscosity of the slurry was studied. The result showed that absolute value of zeta potential would be lower in the concentrated suspension or suspension with organic binder. The release of NH3 during ball milling would increase the pH value, while the dissociation of the soluble SiO2 would increase it during setting. The gel time of the suspension was significantly affected by the organic binder addition. Higher pH value and lower solid loading was conductive to obtain slurry with lower viscosity.